A study on clinical profile of acute undifferentiated febrile illness in a tertiary care hospital - I., Mariraj; Adil, Mohammed; M., Ramkumar; M., Jagadeesan; S., Prasanna Karthik; R., Kannan; J., Damodharan; M., Vivekanandan (International Journal of Advances in Medicine, 2020)
Background: Acute febrile illness is very common among patients seeking hospital care in tropical country like India. This study was conducted to evaluate etiology and clinical profile of Acute Undifferentiated Febrile Illness (AUFI) in a tertiary care hospital. Methods: This study was conducted in 175 patients with acute febrile illness who were admitted in the medical wards and ICU from January 2018 to June 2019 in a tertiary care hospital. Clinical examination and investigations like complete hemogram, liver function test, renal function test, smear for malarial parasite, widal test, urine analysis blood and urine culture, antibody titters for dengue, Leptospirosis and imaging were done. Results: Out of 175, 94 (54%) were males and 81 (46%) were females. The commonest etiology was dengue (19%) followed by enteric fever (18%), scrub typhus (16%), malaria (14%), tuberculosis (6%) and leptospirosis (5%). 138 (79%) patients had less than 14 days of fever of which dengue was the most common and 37 (21%) patients had more than 14 days of fever with tuberculosis being predominate. Other common symptoms were chills/rigors, headache and myalgia seen in 77%, 71% and 42% respectively. Icterus was seen in malaria (42%) and leptospirosis (38%). Elevated transaminases levels were observed with dengue, leptospirosis, scrub typhus, enteric fever and malaria. ARDS was most common in scrub typhus. Conclusions: Among acute febrile illness, dengue and enteric fever were the most common in this study. A thorough and probing search for an eschar is very important in scrub typhus. The treating physician has to keep in mind the comprehensive list of differential diagnosis for patients with febrile illness and anticipating the complications.